Attention-Deficit/Hyperactivity Disorder (ADHD) - Garret D. Evans; Heidi Liss Radunovich (EDIS)
Revised! FCS-2134, a 4-page fact sheet by Garret D. Evans and Heidi Liss Radunovich, lists the signs of ADHD and describes when the signs are considered to be ADHD. This version is updated with current statistics throughout and includes a section on what to do if you suspect ADHD, and includes additional resources for information and assistance, plus an expanded reference list. Published by the UF Department of Family Youth and Community Sciences, August 2006.